DATOK INSTITUTE LAKSAMANA WEAVING MOTIVES OF MALAY SONGKET WEAVING IN LANGKAT: STUDY OF LOCAL WISDOM CHARACTER EDUCATION MODELS - Lubis, Hasrita; Nurhayati, Nurhayati; Sumantri, Pulung; Hardiyansyah, Muhammad Ricky; Nababan, Surya Aymanda; Nugraha, Muhammad Adika (Universitas Negeri Medan, 2023)
The Datok Laksamana Institute for Typical Malay Songket Weaving in Langkat Dusun V Plantation Village, Tanjung Pura Langkat District, has been revitalized since 1986 by the Government through training for development. Directional development explores local wisdom that has existed since the mulda of the Langkat sultanate around the 18th century. This type of qualitative descriptive research is a research method that utilizes qualitative data and is described in descriptive history. This type of qualitative descriptive research is often used to analyze events, phenomena, or situations socially. This type of qualitative descriptive research is a combination of descriptive and qualitative research. Qualitative descriptive research displays the results of the data as they are, without manipulation or other treatment. The institution empowers members of the local community, so Langkat's unique woven motifs have succeeded in identifying 144 beautiful woven motifs. These motifs are extracted from culture and natural raw materials with high artistic and philosophical values that have thrived in people's lives and are woven into woven motifs. This study of noble-valued weaving motifs is full of essential values and is a guide for the Langkat Malay community in carrying out noble life stages and tasks such as traditional wedding attire, respecting guests, circumcision events, and so on. Within the 144 motifs that are related to the meaning of a typical life value, there can be a model that is able to build a strong personality. In this study, three typical motifs will be discussed: teni grass, Diving duck, and Tepak Sirih. The meaning of the philosophy or value contained in each motif is different. The value of these motifs is very humane, so they remain relevant from time to time. The traditions of the people, with their natural environment interweaving traditions in various aspects of life, are fought for to be passed on to the next generation. The realization of the meaning of culture conveyed by Ki Hajar Dewantara is that culture requires values of struggle to be developed by an independent spirit. The struggle to preserve cultural values in the 21st century faces opportunities and challenges. Society is internally challenged by the arrival of a global culture with technology that enters the soul aspects of the young generation in an unlimited way. Opportunities are directed by the government to explore traditional values to be developed within the education system as a characteristic of the nation's character. Optimizing oneself to become a whole person with the uniqueness of each ethnicity to become a resilient world community is the ideal of the Unitary State of the Republic of Indonesia.